THE CONTRIBUTION OF HUMAN CAPITAL AND STRUCTURAL CHANGE TO EAST JAVA’S ECONOMIC GROWTH: : DOES THE STRUCTURAL CHANGE BETTER THAN HUMAN CAPITAL? - Listiono (East Java Economic Journal, 2019)
This paper investigates the effect of human capital and structural changes on economic growth in East Java using panel data from 38 districts/cities during 2010-2015. The estimation results using the Generalized Method of Moment (GMM) Arellano-Bond show that health and education as indicators of human capital have a positive and significant effect on economic growth. In addition, structural changes as measured by the share of labor, especially in the industrial, construction, and services sectors have a positive and significant impact on economic growth. Interestingly, this study found evidence that structural changes have a greater effect than human capital.